Purification and biochemical characterization of a novel acido-halotolerant and thermostable endochitinase from Melghiribacillus thermohalophilus strain Nari2AT. (1st February 2019) - Mohamed, Sara; Bouacem, Khelifa; Mechri, Sondes; Addou, Nariman Ammara; Laribi-Habchi, Hassiba; Fardeau, Marie-Laure; Jaouadi, Bassem; Bouanane-Darenfed, Amel; Hacène, Hocine
Abstract: An extracellular acido-thermostable endochitinase (called ChiA-Mt45) from thermohalophilic Melghiribacillus thermohalophilus strain Nari2A T gen. nov. sp. nov., was purified and biochemically characterized. The maximum chitinase activity recorded after 48-h of incubation at 55 °C was 9000 U/mL. Pure enzyme was obtained after heat treatment (20 min at 90 °C) followed by sequential column chromatographies on fast performance liquid chromatography (FPLC) and high performance liquid chromatography (HPLC). Based on MALDI–TOF/MS analysis, the purified enzyme is a monomer with a molecular mass of 45201.10 Da. The 27 residue NH2 -terminal sequence of the enzyme showed high homology with Bacillus GH-18 chitinases family. The optimum pH and temperature values for chitinase activity were pH 3.5 and 90 °C, respectively. In addition, the enzyme was halotolerant and can be classified as an extremozyme. The pure enzyme was completely inhibited by p -chloromercuribenzoic acid ( p -CMB) and N -ethylmaleimide (NEM). Its K m and k cat values were 0.253 mg colloidal chitin/mL and 47000 s −1, respectively. Interestingly, its catalytic efficiency was higher than those of chitinases ChiA-Hh59 from Hydrogenophilus hirchii KB-DZ44 and chitodextrinase from Streptomyces griseus, and N -acetyl-β-glucosaminidase from Trichoderma viride . The studied chitinase exhibited high activity towards colloidal chitin, chitin azure, glycol chitin, while it did not hydrolyse chitibiose and amylose. Additionally, thin-layer chromatography (TLC) analysis from chitin-oligosaccharides showed that ChiA-Mt45 acted as an endosplitting enzyme. Overall, the chitinase ChiA-Mt45 may have great potential for the enzymatic degradation of chitin. Graphical abstract: Image 1 Highlights: Purification of chitinase (ChiA-Mt45) from M. thermohalophilus Nari2A T was carried out. The molecular weight and the NH2 -terminal sequence of the chitinase was determined. Optimum pH and temperature values for activity were pH 3.5 and 90 °C, respectively. The kinetic parameters and the TLC of hydrolysis products of the enzyme were studied. ChiA-Mt45 may be used as potential candidate for the enzymatic degradation of chitin.